Schedule Thinning Following Functional Communication Training: Effects of Chained and Multiple Schedules. Issue 5 (September 2022) - Nuhu, Nadrat N.; Pence, Sacha T.
Functional communication training (FCT) is used to reduce rates of problem behavior by teaching communicative responses that access functionally equivalent reinforcers. During FCT, the communicative response is typically placed on a dense schedule of reinforcement that is unlikely to be maintained in the natural environment. Experiment 1 evaluated the effects of two schedule-thinning procedures (chained schedules and multiple schedules) on problem behavior maintained by escape from demands for three participants following FCT. The chained and multiple-schedule procedures were effective in reducing rates of problem behavior. Compliance increased under both schedules, but the chained schedule resulted in higher levels of compliance with two participants. In Experiment 2, participants' preference for the chained or multiple-schedule procedure was evaluated using a modified concurrent-chain procedure. One participant preferred the chained schedule. One participant preferred the multiple schedule. One participant did not appear to discriminate between conditions.